Parent-focused child therapy : attachment, identification and reflective functions. - Wachs, Carol, ....-; Jacobs, Linda, ....- (Lanham : Rowman & Littlefield, 2006)
Today more pediatric therapists are centering their work on the parent-child relationship and are turning to parents as a primary modality in solving children's problems. Parent-Focused Child Therapy: Attachment, Identification, and Reflective Functions is an edited collection, drawing from leading psychotherapists with specialties in family therapy. Carrol Wachs and Linda Jacobs tap into the current literature on the efficacy of working with parents in therapy situations. The collected essays in this book, from renowned psychotherapists, focus on identifying and evaluating a variety of approaches and their effects on standard questions of attachment, identity, and reflection in dealing with children in therapy. Parent-Focused Child Therapy is especially attractive given its currency, integrating relational theory, attachment theory and infant research.
Keywords: Kinderpsychotherapie; Ouder-kindrelatie.; Ouderparticipatie